The Confusion Of Sexual Orientation Reflected In HanifKureishi's The Buddha Of Suburbia (1990): A Sexual Orientation Theory - Megawati, Wiwik, Dr. M. Thoyibi, M.S, Nur Hidayat, M.Pd (2014)
The aim of this research is to analyze how the confusion of sexual orientation expressed in the novel, to analyze the cause of the confusion expressed in the novel and to analyze the confusion of sexual orientation by using a sexual orientation theory. This research is a qualitative research. Technique of analyzing data is descriptive analysis. The method of collecting data are (1) reading the novel repeatedly and understanding the content. (2) Giving marks to particular parts both primary and secondary data sources. (3) Taking notes for important parts both primary and secondary data sources. (5) Classifying the data into categories and developing them into a good unity. (6) Drawing conclusion and formulate its pedagogical implication. Based on the sexual orientation theory analysis, it can be concluded that the major character often find the confusion in determining his sexual orientation whether homo, hetero or bisexual. There are some expressions of the confusion sexual orientation seen from homosexual, heterosexual and bisexual perspective. The confusion caused by environment, divorce, religion and spirituality